Perlindungan Terhadap Hak-Hak Anak Angkat Dalam Pembagian Harta Waris Perspektif Kitab Undang-Undang Hukum Perdata Dan Hukum Islam - Al-Ghazali, Muhammad (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
Protection of the rights of adopted children in the matter of property inheritance in the perspective of book of civil law and Islamic law. Adoption in civil law is an act which equalized adopted children with birth children, both in terms of caring and inheritance (Articles 11,12,13 and 14 of Stb. 1917 No. 129). In Islamic law, adoption will not result in a blood relationship and do not become the basis and cause of inheritance, because the basic principle of the heir is a blood relation. This article examines: 1. What is the legal position of adopted child in the matter of property inheritance in the perspective of book of civil law and Islamic law? 2.Which of the two legal systems that provide adequate protection for adopted child? This type of research is library research, with qualitative methods, and normative juridical approach. The result is; the legal position of adopted child for the right of inheritance in the Book of Civil Law has the same status as the heirs for an inheritance. But according Stb. 1917 No. 129, this provision provides that the limitation of the adopted child only becomes heir on the part that are not mentioned in the wills. Being in Islamic law, the position of adopted children can not be equated with birth children, they can not receive inheritance from the adoptive parents, and vice versa, but the children may receive the will treasure. In between the legal system, Islamic law provides adequate protection to the adopted children, because it has a child care institution.